The Effectiveness of Interactive Digital Media in Enhancing Students’ Competence in Hair Bun Styling Instruction - Israwati Hamsar (Academic Bright Collaboration, 2025)
This study aimed to examine the effectiveness of video-based interactive digital media in enhancing students’ competence in hair bun styling instruction within cosmetology education. Grounded in Mayer’s Cognitive Theory of Multimedia Learning and Bandura’s Social Learning Theory, the study addresses the need for more engaging, flexible, and repeatable instructional approaches in practice-based vocational learning environments. A quasi-experimental study employing a non-equivalent control group design was conducted involving 12 undergraduate students enrolled in the Family Welfare Education Study Program. Baseline equivalence between the experimental and control groups was confirmed through comparable pretest results. The experimental group received instruction through researcher-developed interactive multimedia modules containing procedural video demonstrations, replay functions, segmented guidance, and zoomed visualizations, while the control group was taught using conventional demonstration methods. The intervention was conducted across four instructional sessions over four consecutive weeks. Data were collected using a performance-based practical assessment rubric and analyzed using descriptive statistics, N-Gain analysis, paired and independent sample t-tests, and Cohen’s d effect size analysis. The findings revealed that the experimental group achieved higher posttest scores (M = 85.83) compared to the control group (M = 72.50). The N-Gain score of the experimental group (0.62) was categorized as moderate-to-high, whereas the control group (0.28) was categorized as low. Statistical analysis showed a significant difference between groups (p < 0.05) with a large practical effect size (Cohen’s d = 1.84). The findings indicate that interactive digital media effectively improves procedural understanding, psychomotor performance, and aesthetic competence in hair bun styling instruction. Although the small sample size and contextual nature of the intervention limit broader generalization, this study contributes empirical evidence supporting the integration of multimedia learning technologies into vocational cosmetology education and provides a foundation for future research involving more advanced digital learning environments.